Aptamer Selection Technology and Recent Advances - Michael Blind; Michael Blank (Elsevier, 2015)
Over the last decade, aptamers have begun to find their way from basic research to diverse commercial applications. The development of diagnostics is even more widespread than clinical applications because aptamers do not have to be extensively modified to enhance their in vivo stability and pharmacokinetics in diagnostic assays. The increasing attention has propelled the technical progress of the in vitro selection technology (SELEX) to enhance the efficiency of developing aptamers for commercially interesting targets. This review highlights recent progress in the technical steps of a SELEX experiment with a focus on high-throughput next-generation sequencing and bioinformatics. Achievements have been made in the optimization of aptamer libraries, separation schemes, amplification of the selected libraries and the identification of aptamer sequences from enriched libraries.